An Oversupply of Law Graduates? Putting the Statistics in Context - Christine Parker (Legal Education Review)
In the last 12 months there have been a spate of stories in the press warning us of an impending “glut” of lawyers. The most frequently quoted “fact” is that there are as many law students as there are lawyers. Professor Bob Williams of Monash University has warned that the growing number of law students is a “potential catastrophe”, and the Queensland Attorney-General has predicted that “we will end up in the same situation as California, where large numbers of lawyers are wandering around ... looking to create work” by “ambulance chasing” or touting. But further research into statistical trends for Australian lawyers and students indicates that the real story is more complex and less alarming than the headlines suggest. First, careful collection of statistics shows that it is simply not true that there are almost as many law students as lawyers in Australia. Secondly, the argument that there are too many law students is fundamentally flawed because it assumes that all law students become lawyers, without sufficiently defining the term “lawyers”. It also fails to take account of graduation rates, attrition from the profession and the number of graduates who do not remain in the law. Finally, reports of the student “glut” have taken an ahistorical approach to the statistics and failed to examine the past ratios of students to lawyers. The purpose of this paper is to set out the statistics as accurately as possible for analysis and planning. Accurate statistics on law students and where they go after graduation, as well as the composition of the legal industry, are necessary in order to plan for legal education and to make judgments on the future prospects of law graduates.